The Chinese concept of face : an exploration of conceptual fashion as a means of critiquing the social phenomenon of lian/mian : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Chen, Qinglin (Massey University, 2021)
Radu Stern mentioned in his book Against Fashion (2004), that fashion is the “sign of class ambition”, the weapon of capitalism, demonstrating that fashion has an inseparable relationship with society. The Chinese concept of face (lian/mian), in sociological terms, broadly represents the prestige and reputation of people, having similar but not exactly the same functions as fashion. The social effect of the Chinese concept of face is not all positive, indeed it leads to many social issues, so my aim is to use fashion to reflect on lian/mian in a global society. Furthermore, I will use experimental and conceptual fashion as my practice method to demonstrate the collaboration between culture and fashion. Conceptual fashion is a derivative of conceptual art defined by Hazel Clark as innovative and experimental, and as an idea and a self-reflection (67). Examining case studies of how other fashion designers communicate cultural concepts through fashion has provided opportunities for analysis, and comparison with my own experience.
Figure 2 is ©2020 Walker Art Center, but re-used for educational purposes only. Other copyrighted images remain for the sake of clarity or access, but may be removed upon request by the copyright holder.
Keywords: conceptual fashion; conceptual art; Chinese concept of face; lian; mian; 'Gain face'; 'Loss face'; 330315 Textile and fashion design